Sialic acids in the extracellular polymeric substances of seawater-adapted aerobic granular sludge. (15th May 2019) - de Graaff, Danny R.; Felz, Simon; Neu, Thomas R.; Pronk, Mario; van Loosdrecht, Mark C.M.; Lin, Yuemei
Abstract: Sialic acids have been discovered in the extracellular polymeric substances (EPS) of seawater-adapted aerobic granular sludge (AGS). Sialic acids are a group of monosaccharides with a nine-carbon backbone, commonly found in mammalian cells and pathogenic bacteria, and frequently described to protect EPS molecules and cells from attack by proteases or glycosidases. In order to further understand the role of these compounds in AGS, lectin staining, genome analysis of the dominant bacterial species, and shielding tests were done. Fluorescence lectin bar-coding (FLBC) analysis showed an overlap with protein staining, indicating presence of sialoglycoproteins in the EPS matrix. Genome analysis gives a positive indication for putative production of sialic acids by the dominant bacteria Candidatus Accumulibacter . FT-IR analysis shows upon selective removal of sialic acids a decrease in carbohydrates, extension of the protein side chain, and exposure of penultimate sugars. Enzymatic removal of sialic acids results in the removal of galactose residues from the EPS upon subsequent treatment with β-galactosidase, indicating a linkage between galactose and sialic acid at the terminus of glycan chains. This work indicates the importance of sialic acids in the protection of penultimate sugar residues of glycoproteins in EPS, and provides basis for future research in the composition of EPS from biofilms and granular sludge. Graphical abstract: Image 1 Highlights: Sialic acids are present in the EPS of seawater-adapted aerobic granular sludge. Sialoglycoproteins in the EPS contain sialic acids as the terminal sugar residue. Ca. Accumulibacter are indicated to be capable of sialic acid production. Terminal sialic acids protect galactose residues in the granule EPS.